ANALISIS JARINGAN JALAN DAN PENENTUAN RUTE TERBAIK BERBASIS SISTEM INFORMASI GEOGRAFIS - Raharjo, Nain; Lestari, Agustin Dita (Teknik Sipil Universitas Negeri Padang, 2024)
Roads are transportation infrastructure that serves as a path for the movement of people, goods, and services to and from certain locations. Apart from being a transportation facility, roads have a role as a tool for regional development and connectivity, as well as environmental functions. Of course, with the complexity of these roles, a road must have a good level of comfort, safety, and travel effectiveness for all users. Nowadays, road users tend to look for the best alternative routes to get the best accessibility with the aim of reducing travel time and avoiding congestion. This study aims to determine the best route, and the ideal travel distance based on several supporting parameters. The method used is the weighting / scoring method for each criterion and then geographic information system-based data processing so that a route map will be obtained. From the results of the analysis that has been carried out, 2 routes are obtained that can be used as alternative routes. The results of the most effective and efficient route analysis based on geological structure, lithology, soil type, road geometry, traffic conditions, land cover, forest environment, slope, and rainfall, found that route 1 with a distance of 17 km, with a total land suitability of 553352613,002664 m2, is the most effective and efficient route, although with a longer distance duration than route 2 which only has a distance of 13 km, with a land suitability level of 100543589,17874 m2.